A MULTI-FACTOR SCORING APPROACH TO RISK ASSESSMENT AND MITIGATION IN SMALL BUSINESS ENTITIES: EVIDENCE FROM UZBEKISTAN (International scientific-electronic journal “Pioneering studies and theories”, 2026)
Small business entities are disproportionately exposed to operational and financial risks owing to constrained resource bases and heightened sensitivity to macroeconomic fluctuations. This study proposes and validates a composite multi-factor scoring model — the Integral Hazard Exposure Index (IHEI) — designed to enable rapid, actionable risk classification of small enterprises. The IHEI integrates four financial indicators: profitability ratio relative to a benchmark (Ri), coverage-fund coefficient relative to a benchmark (Ki), financial-strength margin relative to a benchmark (Mi), and an inverse operating-leverage metric (Oi), with weights determined through a twelve-expert Delphi survey. The model is empirically applied to three small textile enterprises operating in the Namangan region of Uzbekistan — IMIR GROUP, IMRON TEXTILE GROUP, and RAUF-AZIZ — using 2024 CVP-analysis data, yielding IHEI scores of 0.885, 0.848, and 0.809, respectively, classifying them in risk zones B and C. Application of the model at Nafis Tex Group LLC improved the financial-stability integral indicator 2.5-fold (from 0.0724 to 0.1798), increased overall profitability by 4.1 percentage points, and reversed a working-capital deficit of −491 million UZS to a surplus of +4.1 billion UZS by 2025. Regression analysis confirms that accounts-receivable velocity, inventory volume, and credit interest rate explain 88% of liquidity variance (R² = 0.88). Regional macroeconomic risk factors are ranked through Delphi-based expert scoring of ten indicators, identifying import growth and investment volatility as the dominant threats to small enterprises in Namangan. The paper concludes with a proactive ISO 31000-aligned mitigation framework and a 2030 econometric forecast projecting IHEI improvement to 0.95+